(untitled) (LIS TODAY, 2024)
This study investigates the awareness and usage of open-source plagiarism checking software among research scholars in the Social Sciences discipline at Lalit Narayan Mithila University (LNMU), Darbhanga, Bihar. Given the increasing importance of academic integrity, this study aims to identify the level of knowledge, usage patterns, and perceived benefits of these tools among researchers. A structured questionnaire was administered to 60 participants, revealing a moderate level of awareness but limited usage. The findings suggest the need for enhanced training and institutional support to promote the effective use of open source plagiarism detection software. Although there is a notable intention to use plagiarism detection resources, various barriers remain that must be addressed to optimize their utilization and reinforce academic integrity in research practices.